Cláusula compromissória institucional nos contratos de franquia - Mendes, Karen Cristina Moron Betti (2014)
The object of study of this work is to present the institutional arbitration as a dynamic and harmonic alternative for the settlement of disputes in dealings relating to contracts of franchises. Justifying this work, with ballast in that, given the dynamics of the relationship in the business world, the internationalization of trade, the agility and speed with which such relations are given, especially in the segment of franchising, there are at least three identifiable assumptions plan, that need to be preserved in the case of solving work in franchising: the expertise of the judge in the matter; the rapid solution of the conflict and the maintenance of good business relationship after the conflict solved, what you get in line of identity, to apply the arbitration as an effective method in this intention. By the way, will be analyzed in this work both institutes, first separately, and after, in their points of confluence, as well as bringing to the fore the controversial aspects that may arise in this relationship of mutualism, which in the course of the study are dissolved, through security keys presented to get the effectiveness and validity of the application of the method do not state, duly harmonized to the franchise, and, finally, suggesting legislative amendment to the law of franchises to guarantee the effective use and valid arbitration in the segment of franchises.